Tribology, performance and emissions of a two stroke-cycle engine using bio-based lubricant / Muhammad Zulfattah Zakaria - Muhammad Zulfattah , Zakaria (2021)
Two-stroke (2T) gasoline engine is labelled as main contributor to air pollution, especially in the city. Ironically, this engine is still being sold and used and its sales was reported to increase over the years. The reason is that 2T gasoline engine is more powerful than four-stroke engine in term of power-to-weight ratio. Advancements in 2T engines technology also produces better emissions than their four-stroke counterpart. Most 2T engines do not have oil sump for lubricant which makes the maintenance easier, cheaper, and more practical e.g., for marine outboard engine which is heavy and costly to be dismantled and brought onshore for service. Unfortunately, majority of 2T lubricant is made of mineral base oil which contributes to the increase of carbon footprint. Bio-based lubricant is claimed and proven to be more environmentally friendly. Mass production of fats especially vegetable fats e.g., palm oil, canola, sunflower and non-edible oils like jatropha, neem and the like has made the conversion of the over-production to be converted into biodiesel and lubricant. Palm oil is currently the most economically wise to be converted into fuel and lubricant. It contains mainly of palmitic acid (C16:0) and oleic acid (C18:1) as well as some traces of other fatty acids. The existence of beta-hydrogen on C18:1 makes oleic acid more oxidation stable and better lubricity than single-hydrogen bond on C16:0. Thus, oleic acid has been chosen to be esterified with alcohols to turn it into polyol ester. The selected alcohol candidates including two-branched structure Neopenthylglycol (NPG) into Neopenthylglycol Dioleate (NPGDO), three-branched structure Trimethylolpropane (TMP) becoming Trimethylolpropane Trioleate (TMPTO), and four-branched structure Pentaerythritol (PE) into Pentaerythritol Tetraoleate (PETO). All three esters were measured for physicochemical properties to conform their lubricant properties standard. They were then mixed with certain percentages of mineral base oil to inherit naphthenic properties of mineral base oil and is proven to exhibit good miscibility with polyol ester and further increases the lubricant lubricity. The blends were then undergone tribo-tests via Fourball-tribotester (FBT) and High Frequency Reciprocating Rig (HFRR) to measure their lubricity performance and were reported in terms of wear scar diameter (WSD) and coefficient of friction (COF). The samples were also optically scanned via Surface Electron Microscopy (SEM) to characterize the wear profiles and Energy-dispersive X-ray Analyzer (EDX) to check for elemental identification and quantitative compositional information on the contact surface. The tribological performance of esters were then compared with the reference synthetic 2T lubricant. Ultimately, the blend composition was again measured via Response Surface Methodology (RSM) to further optimize the properties of blends. The predicted responses were compared with experimental values and the results were reported and intensively discussed. Engine testing was then performed to check the emissions and carbon deposition on the spark plug as well as the engine performance.